BCI glossary and functional model by the IEEE P2731 working group. Issue 3 (3rd July 2021) - Easttom, Chuck
ABSTRACT: The IEEE P2731 working group has spent much of 2020 working on a lexicography for Brain Computer Interface research. Concomitant with that glossary, has been work on a functional model for BCI. This special issue contains articles written by teams of the P2731 working group, each focusing on a different aspect of that functional model.